Comparative Analysis of the Performance of Seedlings of Some Forest Tree Species Under the Influence of Fertilisers - Singh, T. P.; Paliwal, G. S. (Indian Forester, 1989)
Analysis of growth responses of seven broad-leaved tree species under various fertiliser treatments in the nursery conditions indicate that fertiliser applications lead to a marked improvement in growth response as determined by parameters like seedling height, stem girth, as well as the widlh and length of the leaves.